The effectiveness of proposed computerized electronic program according to the method of mastery learning on academic achievement in the subject of educational technique principles at the basic education stage- Sudan - Edris Kamtor Al hassan , Esam (Journal of College of Education, 2019)
The aim of this research is to identify the effectiveness of proposed computerized electronic program according to the method of mastery learning on academic achievement in the subject of educational technique principles at the basic education stage. The quasi -experimental method and achievement test were used as a tool for data collection, The research population comprised of pupils of grade of the eighth in the basic education stage in Um Baddah Locality, Khartoum State, which consists of 30 schools. The total survey was conducted by Rabaa Al-Adawiya Girls School to represent the 50 pupils of the research sample, they were randomly divided into two groups, controlled and experimental groups,(25) pupils for each group. The appropriate statistical methods were used to analyze the data by using SPSS.The research concluded that there are statistically significant differences at the level of significance (0.05) between the average achievement scores in the subject of educational technique  principles for the eighth grade pupils in the basic education stage between the control group that have been studied to the traditional method and the experimental group that has been studied by using computerized electronic program designed according to the method of mastery learning in the post-test in favor of the experimental group. there are statistically significant differences at the level of significance (0.05) between the average achievement scores in the subject of educational technique  principles for the eighth grade pupils in the basic education stage between the control group that have been studied to the traditional method and the experimental group that has been studied by using computerized electronic program designed according to the method of mastery learning in the post-test in favor of the experimental group at the level of recalling and level of understanding.Based on the results of the research, the researcher recommended; the importance of producing instructional programs interactive computerized in order to benefit in the teaching of educational technique  principles subject at  the basic education stage. Introducing the e-learning system accordance to the strategy of mastery learning in Sudanese basic education schools. The need to pay attention to the training of teachers of the basic education stage on the basis of the design of computerized instructional programs  and employment in teaching.